2020
DOI: 10.1002/acp.3722
|View full text |Cite
|
Sign up to set email alerts
|

Creating nonbelieved memories for bizarre actions using an imagination inflation procedure

Abstract: The current experiments examined the creation of nonbelieved true and false memories after imagining bizarre and familiar actions using the imagination inflation procedure (Goff & Roediger, 1998). In both experiments, participants took part in three

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 27 publications
5
29
0
Order By: Relevance
“…For example, in a student sample who had an experience of NBM ( N = 98), it has been found that 56% ( n = 55) of reported nonbelieved memories were formed because of negative social feedback, such as being told by family members or friends that the event never happened (Mazzoni et al, 2010). In experimental settings, negative social feedback has been proven to be a powerful means to create nonbelieved memories (Li et al, 2020; Otgaar et al, 2018). For example, in Otgaar and colleagues' experiment (Otgaar et al, 2018), participants first viewed a set of scenes (e.g., city square or a pub) in a virtual reality setting and rated the characteristics of these memories the next day using an online questionnaire.…”
Section: Trait Memory Distrust and Memory Errorsmentioning
confidence: 99%
“…For example, in a student sample who had an experience of NBM ( N = 98), it has been found that 56% ( n = 55) of reported nonbelieved memories were formed because of negative social feedback, such as being told by family members or friends that the event never happened (Mazzoni et al, 2010). In experimental settings, negative social feedback has been proven to be a powerful means to create nonbelieved memories (Li et al, 2020; Otgaar et al, 2018). For example, in Otgaar and colleagues' experiment (Otgaar et al, 2018), participants first viewed a set of scenes (e.g., city square or a pub) in a virtual reality setting and rated the characteristics of these memories the next day using an online questionnaire.…”
Section: Trait Memory Distrust and Memory Errorsmentioning
confidence: 99%
“…A classical study showed that participants misremembered seeing a “stop” sign after they received a verbal misleading information while in fact there was a yield sign ( Loftus, 1975 ). More recent studies showed that encoded memories could be undermined or weakened after receiving false (verbal) feedback ( Mazzoni et al, 2014 ; Otgaar et al, 2014 ; Wang et al, 2017 , 2019 ; Li et al, 2020 ). For example, after participants performed actions such as clapping their hands in front of a video camera, their memories of the performed actions were tested a few days later, and false feedback was provided telling participants that their memories were wrong and some actions were never performed ( Mazzoni et al, 2014 ).…”
Section: Manipulating Memory Associations Mimimizes Avoidance Behaviormentioning
confidence: 99%
“…Non-believed memories are also the topic of two additional papers in this issue. NBMs are directly examined by Li and colleagues (Li, Wang, & Otgaar, 2020), who test whether they can refer also to bizarre actions, rather than common and mundane actions. Investigating some of the boundaries of the possible contents of NBMs is per se an interesting question.…”
Section: The Paper Proposes a New Comprehensive Model That Representsmentioning
confidence: 99%
“…It would be crucial to understand whether children who report having performed violent and rather unbelievable actions report false memories for actions never performed. The paper by Li et al (2020) represents an attempt to address, even if from afar, this issue and understand whether false memories for bizarre/incredible actions can be implanted. There are some papers already addressing this question, one also in Italian (Casciano, Mazzoni, & DeLeo, 2004) The question is: do we believe that the mental scenarios we create about future events represent real possibilities and the events will happen?…”
Section: The Paper Proposes a New Comprehensive Model That Representsmentioning
confidence: 99%